A Call for Greater Attention to Culture in the Study of Brain and Development. (March 2021) - Qu, Yang; Jorgensen, Nathan A.; Telzer, Eva H.
Despite growing research on neurobiological development, little attention has been paid to cultural and ethnic variation in neurodevelopmental processes. We present an overview of the current state of developmental cognitive neuroscience with respect to its attention to cultural issues. Analyses based on 80 publications represented in five recent meta-analyses related to adolescent developmental neuroscience show that 99% of the publications used samples in Western countries. Only 22% of studies provided a detailed description of participants' racial/ethnic background, and only 18% provided for socioeconomic status. Results reveal a trend in developmental cognitive neuroscience research: The body of research is derived not only mostly from Western samples but also from participants whose race/ethnicity is unknown. To achieve a holistic perspective on brain development in different cultural contexts, we propose and highlight an emerging interdisciplinary approach—developmental cultural neuroscience—the intersection of developmental psychology, cultural psychology, and cognitive neuroscience. Developmental cultural neuroscience aims to elucidate cultural similarities and differences in neural processing across the life span. We call attention to the importance of incorporating culture into the empirical investigation of neurodevelopment.